The pre-start training technique of marksmen-sportsmen in the Olympic exercise RFP - Petriv O. S. (Kharkov National Pedagogical University, 2012)
It is shown the features of the new method prelaunch athletes in high-speed shooting of a standard pistol at five targets, which appear simultaneously at a distance of 25 meters. It is determined that the complexity of the rapid-fire is in necessity to coordinate the exact aiming at the center of the target with a smooth touch of the trigger. The methodology proposed new materials that clarify a system of forming knowledge and skills in the shooting sports. Practical recommendations containing new, scientifically based information to improve the technical and tactical actions of athletes in high-speed shooting of a standard pistol at five targets simultaneously appear at a distance of 25 meters.